Records of non-conformities as planning a quality management system for the establishment of hemotherapy (Research, Society and Development, 2022)
The present study aimed to analyze the records of non-conformities, and to understand the main causes of inaccuracies, in order to guide managers in improving the quality system of the services provided. Method: The present research was of the experimental type, based on internal audits carried out in 2020, in a hemotherapy unit, located in a region of northeast Brazil. Seven environments were evaluated, called sector A, B C, D, F and G, from the application of scripts, manuals and inspection guides. Results: From the internal audit inspection reports, during the month of January to December 2019, 163 non-conformities were found. In relation to January to December 2020, 282 non-conformities were detected. A reduction of 73.6% of quality problems was observed after the completion of the improvement cycle and 49.1% are still pending. Conclusion: The improvement cycle proved to be a valid intervention to increase service adherence to quality management activities recommended by current standards and legislation.